Niacinamide for the treatment of melasma: an integrative review of randomized clinical trials (Research, Society and Development, 2022)
Introduction: Melasma is a very common and difficult to treat hypermelanosis because it usually responds poorly to therapies, negatively affecting the quality of life of patients. Objective: to know and analyze the scientific evidence related to the treatment of patients with facial melasma treated with niacinamide.  Method: a literature review was performed based on a data search in BIREME, PubMed, SciELO and ScienceDirect. Articles indexed in these electronic journals were included in the time frame from 2011 to 2019. Results: Evidence analyzes revealed a major impact on the appearance of facial melasma after niacinamide treatment. Well, the studies (100%) concluded improvement of the spots with the treatment time, improving the appearance of the skin. Conclusion: Evidence shows that niacinamide has a lightening property in adult women with improvement of melanic hyperpigmentation caused by melasma. However, there is very little evidence published in the last decade using pure niacinamide for increased pigmentation in melasma.